Les archives latino-américaines à la BDIC : principaux fonds et thématiques - Cécile Tardy (Nuevo mundo - Mundos Nuevos, 2008)
The Bibliothèque de Documentation Internationale Contemporaine (BDIC) is an academic library which collects and preserves different types of documents about political and social history and international relations in the 20th century. One can find in its collections archives from Latin-American associations, trade-unions, political parties or police authorities, or from associations in sympathy with Latin-American people when they were dominated by military dictatorships. These archives may have been donated to the library, or collected as microfilms or digitized copies thanks to preservation programs. The archives presented in this article are important sources for the study of trade-union activities and political life in Bolivia and Peru, State terrorism of the dictatorships in Uruguay, Bolivia, Paraguay, Brazil or even more Argentina. In the final part of the article, we briefly present the archives of DIAL and the inter-association center “Documentation Réfugiés”, in which can be found documents about political and social history of Latin America.